Legal Analysis of Female Circumcision in The Context of Legal Pluralism in Indonesia - Debby Hasmita; Imam Ropii; Marsudi Dedi Putra (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2026)
This study aims to analyze legal regulations on female circumcision practices from the perspective of legal pluralism in Indonesia and examine the legal implications for women's health protection. The research method used is normative legal research with a qualitative approach, based on the analysis of legislation, legal literature, and expert opinions. The approaches used include a statutory approach, a conceptual approach, and a case approach to examine the relationship among state law, religious law, and customary law regarding the practice of female circumcision. The results of the study show that the Indonesian government, through Law No. 17 of 2023 concerning Health and Government Regulation No. 28 of 2024, has prohibited female circumcision as a form of protection of human rights and reproductive health in accordance with WHO recommendations. However, the practice of female circumcision is still found in society in symbolic and traditional forms, which are considered part of the values of purity and moral obligations. Differences in perception between state law, religious law, and customary law pose challenges in policy implementation. Clarity on the legal boundaries between permissible and prohibited forms of circumcision is necessary to ensure the protection of women and children without causing social resistance in the community.